Outcome analysis of biplanar mandibular distraction in adults - Chattopadhyay, Debarati (Arch Craniofac Surg, 2021)
BACKGROUND: Mandibular deficiency leading to facial asymmetry causes cosmetic deformity as well as psychological stigma for the patient. Correction of these mandibular asymmetries is a major challenge. The study investigates the efficacy of bidirectional mandible distraction for the treatment of mandibular deficiency. METHODS: This prospective study included six individuals aged between 17 and 24.4 years. Five patients had hemifacial microsomia and one had unilateral temporomandibular joint ankyloses. All patients underwent mandibular distraction osteogenesis. Postoperative skeletal changes in affected mandible, and changes in occlusal plane and oral commissure cant were evaluated using three-dimensional reconstruction. Patient satisfaction and understanding of the procedure were assessed through three questionnaires administered during pre-distraction, distraction and post-distraction phases. RESULTS: In pre-distraction phase, aesthetic appearance seemed to be the primary indication for surgery. In distraction phase, pain while chewing was the primary handicap. In post-distraction phase all patients were satisfied with the aesthetic outcome. The facial deformity was improved through mandibular distraction osteogenesis. On the affected side in all the patients, height and length of the mandible increased. Canting of the occlusal plane and oral commissure was corrected. CONCLUSION: Bidirectional mandible distraction is an effective treatment for correction of mandible deformities in adult patients.